016. Prevalence of metabolic syndrome between patients with obstructive sleep apnea - Xanthoudaki, Maria (J Thorac Dis, 2015)
BACKGROUND: Obstructive sleep apnea (OSA) and metabolic syndrome (MS) are highly prevalent disorders among obese middle-aged adults. MS has been associated with OSA. Diagnosis of MS is set after fulfillment of either the National Cholesterol Education Program’s Adult Treatment Panel III (NCEP-ATP III) criteria or the International Diabetes Federation (IDF) criteria. OBJECTIVE: The study was to evaluate and compare the prevalence of MS in moderate and severe OSA patients using both definitions and to assess possible differences between male and female patients. METHODS: Newly diagnosed, moderate-to-severe, consecutive OSA patients were included. Anthropometric characteristics and cardiovascular risk factors were recorded. Both ATP III and IDF criteria were used for diagnosing MS. RESULTS: A total of 410 patients (323 males, 87 females) were included to the study. All the participants underwent overnight polysomnography and were divided into two subgroups, depending on OSA severity. Mean age was 54.9±12.5 years, mean body mass index (BMI) was 35.74±6.88 kg/m(2) and mean AHI was 50.5±24.7/hour. Using the IDF criteria, 41.5% of the patients (n=170) were diagnosed with MS, while using the ATP III definition, 157 patients (38.3%) met the criteria for MS. In moderate (AHI 15-29.9/h) OSA subgroup (n=106), a significant difference was found in MS prevalence between men and women using either ATP III (50% of women vs. 24.3% of men; P=0.021) or IDF criteria (63.3% of women vs. 28% of men; P=0.001). In severe (AHI ≥30/h) OSA subgroup (n=304), the prevalence of MS was significantly higher in women when the ATP III definition was used (52.6% of women vs. 37.4% of men; P=0.037) but not when the IDF definition was used (54.4% of women vs. 39.8% of men; P=0.053). CONCLUSIONS: Among patients with moderate-to-severe OSA, MS is highly prevalent and women are at higher cardiovascular risk. However, the definition is certainly an important factor, as the estimated prevalence of MS can be significantly affected when different criteria of MS (ATP III or IDF) are used.